Assessment Beyond IQ - Omichinski, Donna Riccio; Van Tubbergen, Marie; Warschausky, Seth (Journal of the American Academy of Special Education Professionals, 2008)
A component of a school assessment plan includes traditional IQ testing, often referred to as psychological or psycho-educational testing. Psycho-educational testing can yield information about how a student compares to others in her grade or age group, individual strengths and needs, and recommendations to improve instruction. The intended purpose of intelligence testing is to measure a person’s cognitive abilities. However, current testing practices rely a great deal on a child’s ability to perform the tests physically by pointing to, writing, or speaking a response to the test question. Using this kind of testing to estimate the cognitive abilities of a child with severe physical and speech impairments is like measuring the cognitive abilities of a visually impaired person by their ability to visually read a test question, or using an English language test to measure the IQ of someone who does not speak English. Parents should question whether or not the assessments will meet the three primary standards of reliability, validity and accessibility. Parents’ advocacy efforts will be most effective if they are informed, assertive, cooperative, and specifically emphasize the need for accessible testing procedures.